Makna Teologis Penebusan Rut Berdasarkan Pendekatan Naratif - Priyono, Joko (JURNAL ILUMINASI, 2023)
Theologically, the author of the Book of Ruth focuses on the promised seed or offspring. However, when viewed from its literary form, the narrative of the Redemption of Ruth by Boaz is a unique story and filled with irony. This can be seen from the narrative of Ruth's redemption by Boaz, where someone who is obliged to redeem does not redeem, while someone who is not obliged to redeem does. It should not be Boaz who has the right to redeem Ruth. The author uses a literary approach method, where the interpreter will gain a lot of understanding of the meaning of Biblical texts and this understanding is certainly by the aims and objectives of writing the Book of Ruth. The problem formulation in this research is "What is the theological meaning of the Redemption of Ruth based on a narrative approach?" and this research aims to find out the meaning of Ruth's redemption based on a narrative approach. The results of the research show that God's grace cannot be hindered. Even though the situation during Ruth's time the Israelites experienced a moral and spiritual decline, amid that situation God came with all mercy and hesed to sinful humans.